Estrategias de comunicación política en Facebook, para posicionar la imagen de la asambleísta zamorana Isabel Enrríquez, durante el periodo legislativo 2021-2023 - Chamba Puglla, . Jhojan Oswaldo (2024)
This research analyses the application of communication strategies on Facebook aimed to enhance the concept of the Assemblywoman Isabel Enriquez from the Zamora province during the period 2021-2023. It examines the specific tactics used on this digital platform and their influence on the perception and credibility of the above-mentioned Assemblywoman among the online audience. It is based on the analyses formulated by experts such as López et al. (2020) who refers to social networks such as Facebook that have established a new communicative context between political parties and movements with their voters, becoming preferential tools for the implementation of the communicative strategies of these organizations and political leaders. This paper employs a mixed methodology, analysing the content published on the assemblywoman’s official Facebook page, and relating it to surveys directed to followers and users of the social network. The content analysis identifies the types of posts, approach and discourse that were mostly used, while the surveys measure how exposure to certain messages affects the perception of Isabel Enriquez by Facebook users. A significant relationship is revealed between Facebook user audiences and the image of the assemblywoman, highlighting the role of social networks in shaping public opinion in the digital age. The conclusions highlight the importance of maintaining an efficient planning and execution of ethical and reflective political communication plans on digital platforms, from the need to educate the public in media skills, especially in the online political context. Consequently, recommendations for future research are suggested, aimed at improving the behaviour and digital relationship between citizens and elected officials in order to consolidate the positioning of the political image.